Vulnerable Road Users, Prioritization of Urban Sectors with High Accident Rates: Review and Evaluation Of Methods - Rueda Villar, Omar; Cerquera Escobar, Flor; Pérez Buitrago, Gonzalo (Ingeniería Solidaria, 2019)
Introduction: This article presents a review and analysis of studies that concern research made into “Road infrastructure design models to improve road safety for vulnerable users, prioritizing the high accident zones in Bogota D.C.” Objective: To understand the interrelationship between the vulnerable road users, natural surrounding factors and buildings, based on the determination of the most representative variables for the analysis using Geographic Information Systems (GIS), applied to the prioritization of areas with high accident rates. Methodology: It is based on identifying, through review, the known and unknown updated and important results about accident investigations with regards to vulnerable road users. Results: The use of multivariable correlation – analysis of groupings that are treated with GIS – to identify the main factors associated with the seriousness of traffic accidents related to vulnerable road users, allows for the generation of road infrastructure designs that reduce the risk, based on areas of high frequency of occurrence. Conclusions: The multi-criteria analysis and Geographic Information Systems (GIS), allow for the prioritization of areas with high accident rates not only through the evaluation of the quantity of accidents but also by the evaluation of their conditions, by which causal factors of greater influence are identified. Originality: Development of infrastructure plans that reduce the risk of vulnerable road users being struck by a vehicle. Limitations: The methodology is only applied to urban areas where there is a pre-existing history of accidents.